COVID-19 in Relation to Business and Management: A Bibliometric Analysis - Cruz-Cárdenas, Jorge (2021)
The COVID-19 crisis has generated considerable research efforts in all areas of knowledge, including the area of business and management. This article aimed to describe the body of knowledge generated on COVID-19 regarding business and management to generate the basis for future research. The present study identified 1,751 relevant articles in the Scopus database. The United States, the United Kingdom, and Australia stood out in terms scientific production, whereas the National Natural Science Foundation of China dominated in funding studies. The analysis of the co-occurrence of keywords in the articles allowed the identification of four thematic clusters that correspond to the priorities given by the research: 1) the crisis and use of technology to overcome it; 2) leadership and risk management; 3) impact on the hospitality, tourism, and air transport sectors; and 4) social impact and corporate social responsibility. This article ends by discussing these results and their implications.